2013
DOI: 10.3390/ijms140510298
|View full text |Cite
|
Sign up to set email alerts
|

An Exonuclease III Protection-Based Electrochemical Method for Estrogen Receptor Assay

Abstract: Estrogen receptor (ER), expressed in approximately 80% of primary breast cancer cells, has proven to be a valuable predictive factor of the disease. Herein, by making use of the specific binding of ER to its DNA response elements, we propose an Exonuclease III (Exo III) protection-based electrochemical method for detecting ER proteins. In this assay, the presence of ER can protect the duplex DNA molecules immobilized on an electrode surface from Exo III-catalyzed digestion, resulting in an increased electroche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…676 An exonuclease III protection-based voltammetric assay for ER was designed using a DNA duplex, incorporating an ERspecific sequence, immobilized onto the surface of a gold electrode. 677 The second strand was labeled with methylene blue at the proximal end. The presence of ER protected the duplex DNA molecules from exonuclease III digestion, resulting in an electrochemical signal.…”
Section: Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 99%
See 1 more Smart Citation
“…676 An exonuclease III protection-based voltammetric assay for ER was designed using a DNA duplex, incorporating an ERspecific sequence, immobilized onto the surface of a gold electrode. 677 The second strand was labeled with methylene blue at the proximal end. The presence of ER protected the duplex DNA molecules from exonuclease III digestion, resulting in an electrochemical signal.…”
Section: Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 99%
“…An exonuclease III protection-based voltammetric assay for ER was designed using a DNA duplex, incorporating an ER-specific sequence, immobilized onto the surface of a gold electrode . The second strand was labeled with methylene blue at the proximal end.…”
Section: Electrochemical Analysis Of Proteinsmentioning
confidence: 99%
“…Several experiments have been developed for the comprehension and for the characterization of the mechanism by which ER is activated by ligand and its binding capacity as a homodimer (ER/E2) 2 to a specific DNA consensus sequence (ERE) located upstream of some estrogenic regulated genes. In this way several biophysical tools have been developed to explore the interaction phenomena such as fluorescence anisotropy [6][7][8], surface plasmon resonance (SPR) [9][10][11][12], FRET [13], electrochemical [14][15][16], resonant waveguide [17]. The main objectives were to determine the estrogenic compounds/ER interaction properties [18][19][20], the ER/ER dimerization phenomena [13,21], ER/ERE interaction mechanism and properties under estrogenic stimulation [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have reported that ER binding to the dsDNA molecules that contain the consensus estrogen response elements (EREs) could protect the dsDNA from Exo IIImediated digestion, which formed a basis for constructing an electrochemical biosensor to detect ER proteins [4]. In the present work, we apply the assay method to further investigate the effect of PI3K inhibitor on the ER protein expression.…”
Section: Resultsmentioning
confidence: 94%